Printed and Audio-Visual Media: Can We Use It in Teaching English? - Jennifer Wong (ELT-Lectura, 2016)
The importance of using mass media in the classroom and finding the ways how to use printed andaudio-visual media were the reasons this article presented. Using long personal experience, in-depth study,surveys and questionnaires this study tries to make the ideas in this article more trustworthy. It is a briefdescription of some practical examples and some tips for novice teachers. This study tends to deal with someof the key issues of using media in the classroom. The following issues are open for discussion: theimportance of Media in general and in education in particular; Media are persuasive and pervasive,newspapers, magazines, radio, television and internet in the classroom, etc.